Agronomic capability of mechanized sugarcane planting - Voltarelli, Murilo Aparecido [UNESP]; da Silva, Rouverson Pereira [UNESP]; Zerbato, Cristiano [UNESP]; Silva, Vicente Filho Alves [UNESP]; Cavichioli, Fábio Alexandre [UNESP] (My University, 2014)
The capacity of the mechanized planting of sugarcane to keep the quality standards (mills) is very difficult to be achieved. The external sources of variation make it difficult to be maintained inside the acceptable level over time. Thus, the goal of this study was to evaluate the agronomic performance of mechanised sugarcane planting in two operation shifts using statistical process control. Mechanised planting was performed in an agricultural area state of São Paulo, Brazil. The experimental design was completely randomised with a total of 80 sampling points (replicates), 40 replicates for daytime operation and 40 replicates for night-time operation. The performance of the mechanised set for both operation shifts was evaluated using the following variables and/or quality indicators: number of billets m-1, total number of shoots m-1, number of viable shoots m-1, percentage of viable shoots, and seedling consumption (Mg ha-1). The results showed that the operational quality of mechanised sugarcane planting varied between the day and night shifts. The total number of shoots m-1 exhibited higher variability for the night than for the day shift. All analysed quality indicators of mechanised sugarcane planting were considered not capable (Cp and Pp < 1.33) of meeting the established targets for the day shift, regardless of the process stability.
Keywords: Agricultural machinery; Agronomic performance; Saccharum spp; Statistical process control